Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

DanielAcedo

  • 3 years ago

How would I factor x^4 - 13x^2 + 36 = 0 ? I have NO idea how to do this.

  • This Question is Closed
  1. DanielAcedo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    would I get (x^2 -4x)(x^2 -9x)=0 ?

  2. mominanisar
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    x^4 - 13x^2 + 36 = 0 x^4 - 9x^2-4x^2 + 36 = 0 x^2(x^2-9)-4(x^2-9)=0 (x^2 -4x)(x^2 -9x)=0

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy